2010
DOI: 10.3390/molecules15117699
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Diphenyl Diselenide and Analogs by Mammalian Thioredoxin Reductase Is Independent of Their Gluthathione Peroxidase-Like Activity: A Possible Novel Pathway for Their Antioxidant Activity

Abstract: Since the successful use of the organoselenium drug ebselen in clinical trials for the treatment of neuropathological conditions associated with oxidative stress, there have been concerted efforts geared towards understanding the precise mechanism of action of ebselen and other organoselenium compounds, especially the diorganyl diselenides such as diphenyl diselenide, and its analogs. Although the mechanism of action of ebselen and other organoselenium compounds has been shown to be related to their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 34 publications
0
22
1
Order By: Relevance
“…Here we have not determined the neuroprotective role of diphenyl diselenide and/or the deleterious action of MTZ exposure in terms of mechanism(s); and this fact could limit an analysis more detailed of our results. However, it is well established in other works that the neuroprotective action of this compound, in different animal models, possibly is associated with its potent antioxidant property, which is mediated by its glutathione peroxidase activity and also by its reduction by cerebral TrxR (thioredoxin reductase) (Nogueira and Rocha, 2010; Sausen de Freitas et al, 2010; de Freitas and Rocha, 2011). Corroborating this idea, there is evidence in the literature indicating that diphenyl diselenide molecule is able to cross the blood‐brain barrier and increase the selenium levels in the brain (Maciel et al, 2003; Nogueira et al, 2004; Prigol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Here we have not determined the neuroprotective role of diphenyl diselenide and/or the deleterious action of MTZ exposure in terms of mechanism(s); and this fact could limit an analysis more detailed of our results. However, it is well established in other works that the neuroprotective action of this compound, in different animal models, possibly is associated with its potent antioxidant property, which is mediated by its glutathione peroxidase activity and also by its reduction by cerebral TrxR (thioredoxin reductase) (Nogueira and Rocha, 2010; Sausen de Freitas et al, 2010; de Freitas and Rocha, 2011). Corroborating this idea, there is evidence in the literature indicating that diphenyl diselenide molecule is able to cross the blood‐brain barrier and increase the selenium levels in the brain (Maciel et al, 2003; Nogueira et al, 2004; Prigol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen was demonstrated to be neuroprotective in preclinical and clinical studies (Saito et al, 1998; Yamaguchi et al, 1998; Davalos, 1999) and in a variety of in vitro and in vivo animal models of neuropathological conditions, including ischemia (Dawson et al, 1995; Imai et al 2003; Porciuncula et al, 2003), quinolinic acid- or glutamate-induced excitotoxicity (Porciuncula et al, 2001; Rossato et al, 2002a,b) and exposure to MeHg (Farina et al, 2003; Moretto et al, 2005; Funchal et al, 2006; Roos et al, 2009). The antioxidant activity of ebselen has been tentatively attributed to its GSH peroxidase-like activity (Muller et al, 1984; Wendel et al, 1984) and to its ability to serve as a substrate for mammalian thioredoxin reductase (TrxR), which metabolizes ebselen to its selenol/selenolate intermediate (Zhao and Holmegren, 2002; De Freitas et al 2010). I n vivo treatment with ebselen and diphenyl diselenide can reduce MeHg neurotoxicity in rodents (Farina et al 2003a,b; de Freitas et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of organoselenides has been attributed to their GSH peroxidase-like activity (Muller et al, 1984; Wendel et al, 1984). More recently it has been demonstrated that ebselen is reduced by mammalian thioredoxin reductase (TrxR) forming ebselen selenol/selenolate (Zhao and Holmegren, 2002; De Freitas et al 2010). Selenolate intermediates are potent nucleophiles and can readily react with electrophilic species, including reactive oxygen species (ROS) (Masumoto et al 1996; Zhao and Holmegren 2002)…”
Section: Introductionmentioning
confidence: 99%
“…Such activities include scavenging of free radicals [60], metal complexation [61], or mimicry of natural antioxidant enzymes for the removal of deleterious hydrogen peroxide and alkyl peroxides (e.g., GPx), the so-called bioinspired antioxidants [46]. Interestingly, diselenides and selenides can be substrates in vivo for mammalian thioredoxin reductase (TrxR), furnishing selenols/selenolates, stronger nucleophiles than their sulfur counterparts; as a result, the corresponding selenol has a stronger reducing power than isosteric thiol [62,63].…”
Section: Discussionmentioning
confidence: 99%